The presence of tumour-associated lymphocytes confers a good prognosis in pancreatic ductal adenocarcinoma: an immunohistochemical study of tissue microarrays - Tewari, Nilanjana; Zaitoun, Abed M.; Arora, Arvind; Madhusudan, Srinivasan; Ilyas, Mohammad; Lobo, Dileep N. (BioMed Central, 2013)
Background Tumour-associated lymphocytes (TALs) have been linked with good prognosis in several solid tumours. This study aimed to evaluate the prognostic significance of CD3, CD8 and CD20 positive lymphocytes in pancreatic ductal adenocarcinoma.